Frequency-Based Crack Effect Study on Beams Under Free Vibration Using Finite Element Analysis - SAHU, Ompriya; DAS, Priyadarshi; MUNI, Manoj Kumar; PRADHAN, Nibedita; BASA, Bidyadhar; SAHU, Shishir Kumar (Engineering Transactions, 2024)
A numerical computation-based analysis of the free vibration analysis of uniform beams with rectangular cross-sections is presented in this work using finite element analysis. The approach involves dividing the beam into segments at the crack section, which is then modelled for simulation for eigenfrequencies on the ABAQUS platform. The numerical simulation results are in excellent agreement with the findings of previous research, confirming the efficacy and applicability of the developed beam model. A sequential comprehensive approach towards analysis of the effects of the position and depth of the cracks on the natural frequencies are addressed in numerical results. The research findings confirm that the simulation model is suitable for the vibration analysis of beams or beam-like elements with different cross-sections.